Effect of Solid- State Fermentation Biomass Supplementation to Mixed Substrate on Digestibility and Methane Mitigation in vitro - Patel, Kishan P.; Katole, Shrikant B.; Pandya, P. R.; Sorathia, K. K.; Patel, Srushti (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to assess the effect of supplementation of various levels of solid-state fermentation (SSF) biomass on in vitro digestibility, total gas production and methane production. Eight different types of substrates were prepared viz. SSF0 (control), and the basal substrates supplemented with SSF biomass at 1%, 2%, 3%, 4%, 5%, 6% and 7% replacing mixed cereal straw was designated as SSF1, SSF2, SSF3, SSF4, SSF5, SSF6 and SSF7, respectively. In vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD) were 10.62 and 11.70% higher (P<0.01) in SSF4 treatment than that of SSF0 treatment. In vitro total gas production was increased numerically due to SSF biomass supplementation as compared to control with maximum increment at 5% level, but statistically the change was not significant. Methane production after 24 h of incubation was lowest (P<0.01) in SSF4 treatment, it reduced by 38.4% as compared to control. Results revealed an improved digestibility, gas production and reduced methane production at 4% level of SSF supplementation, and was found to be most suitable level for further in vivo studies in dairy animal.